Implementation and Effect of the Multimodal Psychosocial MAKS Intervention in Day Care Centers for People with Cognitive Impairment: Follow-up Results After the End of the RCT - Grässel, Elmar; Donath, Carolin; Pendergrass, Anna; Luttenberger, Katharina (Gesundheitswesen, 2021)
Zusammenfassung
CRIS-Team WoS Importer:2021-11-12